Abnormal uterine bleeding in women of peri-menopausal age: a retrospective study - Chennuru, Rambabu; Potnuru, Ramkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abnormal uterine bleeding (AUB) is a phenomenon which refers to menstrual bleeding of abnormal frequency, duration or quantity. It is a common gynaecological complaint caused by wide variety of organic or non-organic causes. The objective of the study was to determine the incidence of abnormal uterine bleeding with respect to aetiopathology, demographic variables, treatment options and other medical disorders. Methods: A retrospective study of randomly selected 200 cases of abnormal uterine bleeding between 40–55 years of age during January 2018 to January 2019, in the Dept. of Obstetrics and Gynaecology, in a tertiary care hospital. Demographic details of each patient were recorded and analysed. Patients were evaluated with menstrual history, physical examination, laboratory tests and histological examinations. Patients were followed up from 3 to 8 months. Results: Most common age group presenting with AUB was 40–45 years (65.55%) and mostly (68.33%) belonged to low socioeconomic status. Most of the women were multiparous and menorrhagia was most common presentation. In 60% cases, cause was non-organic (dysfunctional uterine bleeding) and among organic causes fibroid (21%) uterus was most common. Maximum number of patients (75%) was treated surgically and 20% got medical treatment. Conclusions: Abnormal uterine bleeding (AUB) is a common gynaecological manifestation allied with considerable morbidity and significantly affects the patient’s family, personal and social life. Perimenopausal women’s health and quality of life can be maintained and improved through preventive care, life style modification, early diagnosis of risk factor and appropriate treatment.